Pharmacokinetic study on the effect of ligustrazine–tangeretin co‐administration on the pharmacokinetics of ligustrazine and its potential mechanism in rats. Issue 2 (28th February 2023) - Liu, Dandan; Liu, Yunjiao; Qian, Xian; Yang, Junwei; Li, Chengjian; Zhu, Lingfeng; Zhou, Jin
Abstract: Both ligustrazine and tangeretin are usually prescribed in the treatment of cardiovascular diseases, which makes their co‐administration possible. The investigation of the interaction between ligustrazine and tangeretin is necessary for the clinical compatibility of their source herbs. This study aimed to investigate the interaction of ligustrazine and tangeretin during their co‐administration. The pharmacokinetics of ligustrazine (15 mg/kg) was investigated in the presence of 50, 100, and 150 mg/kg tangeretin in rats with six of each. A single dose of ligustrazine was set as the control. The effect of tangeretin on the in vitro metabolic stability of ligustrazine was also investigated in rat liver microsomes. Tangeretin significantly reduced the system exposure of ligustrazine under all experimental concentrations. Specifically, tangeretin reduced the AUC (from 48.86 ± 12.57 to 41.02 ± 4.85 (50 mg/kg tangeretin), 31.47 ± 5.26 (100 mg/kg tangeretin), and 27.55 ± 9.60 (150 mg/kg) μg/mL × h ), MRT (from 7.05 ± 0.26 to 6.33 ± 0.48, 5.53 ± 0.68, and 5.21 ± 1.31 h), C max (from 7.45 ± 0.44 to 6.03 ± 0.44, 5.24 ± 0.47, and 5.02 ± 0.56 μg/mL), and t 1/2 (from 5.90 ± 1.27 to 4.84 ± 1.19, 3.48 ± 1.33, 3.09 ± 0.62 h) in rats. In vitro, tangeretin also reduced the metabolic stability of ligustrazine behaved as the decreased half‐life and increased intrinsic clearance rate. Co‐consumption of ligustrazine with tangeretin induced interactions, which shortens the system exposure of ligustrazine. This study provides theoretical guidance for the clinical prescription of ligustrazine‐ and tangeretin‐containing herbs. Abstract : Co‐administration of ligustrazine and tangeretin induced reduced systemic exposure and metabolic stability of tangeretin via the increasing activity of CYP3A4.